Slope improvement using sheet pile / Muhamad Izzat Rosli - Rosli, Muhamad Izzat (Universiti Teknologi Mara, Perak, 2014)
As a building survey student for UITM Seri Iskandar, I was obligated to do a practical training for semester 6 to finish my diploma studying. I was choose to practical at the Jabatan Kerja Raya Jerantut Pahang from November 2013 to April 2014. While I was practical at JKR Jerantut, there have been several project has undergoing a construction process. The several project are ‘Projek Pembangunan Belia Dan Sukan, Projek Pembinaan Klinik Kesihatan Jenis 3, Projek Pembaikan Jambatan Sg Kenong, Projek Menaik taraf JalanSg Yap-Kg Doja Dan Projek Pembaikan Cerun Di Sekolah Menengah Kebangsaan Jerantut Dan Sekolah Kebangsaan Jerantut Jaya’. Also to completed my practical training, I has been given a responsibilities to do full report about one project that undergo in my practical organization. So, I has choose to do a report about ‘Projek Pembaikan Cerun Si Sekolah Menengah Kebangsaan Jerantut Dan Sekolah Kebangsaan Jerantut Jaya’. I choose this project to do a report because the location of project is near with my office. The project also has been start exactly same with my practical training which is 25 November 2013. This project which is slope also different from what I studying at UITM make me want to studying and following more about this project. This project also will use sheet pile as a retaining wall to retain the soil movement of Sg Betong which are adjoin with two school. The contractor party also will use steel technology to create and construct the bridge steel. The bridge must been construct to make sure the vibrator hammer machine can cross the river to start the piling work. There are very rare slope project that use sheet pile as retaining wall and I decided to choose this project as my report for practical training.